Biomechanical comparison of conventional and anatomical calcaneal plates for the treatment of intraarticular calcaneal fractures – a finite element study. Issue 13 (2nd October 2016) - Yu, Bin; Chen, Wen-Chuan; Lee, Pei-Yuan; Lin, Kang-Ping; Lin, Kun-Jhih; Tsai, Cheng-Lun; Wei, Hung-Wen
Abstract: Initial stability is essential for open reduction internal fixation of intraarticular calcaneal fractures. Geometrical feature of a calcaneal plate is influential to its endurance under physiological load. It is unclear if conventional and pre-contoured anatomical calcaneal plates may exhibit differently in biomechanical perspective. A Sanders' Type II-B intraarticular calcaneal fracture model was reconstructed to evaluate the effectiveness of calcaneal plates using finite element methods. Incremental vertical joint loads up to 450 N were exerted on the subtalar joint to evaluate the stability and safety of the calcaneal plates and bony structure. Results revealed that the anatomical calcaneal plate model had greater average structural stiffness (585.7 N/mm) and lower von Mises stress on the plate (774.5 MPa) compared to those observed in the conventional calcaneal plate model (stiffness: 430.9 N/mm; stress on plate: 867.1 MPa). Although both maximal compressive and maximal tensile stress and strain were lower in the anatomical calcaneal plate group, greater loads on fixation screws were found (average 172.7 MPa compared to 82.18 MPa in the conventional calcaneal plate). It was noted that high magnitude stress concentrations would occur where the bone plate bridges the fracture line on the lateral side of the calcaneus bone. Sufficient fixation strength at the posterolateral calcaneus bone is important for maintaining subtalar joint load after reduction and fixation of a Sanders' Type II-B calcaneal fracture. In addition, geometrical design of a calcaneal plate should worth considering for the mechanical safety in practical usage.